Exploring monovalent and multivalent peptides for the inhibition of FBP21-tWW - Henning, Lisa Maria (Beilstein J Org Chem, 2015)
The coupling of peptides to polyglycerol carriers represents an important route towards the multivalent display of protein ligands. In particular, the inhibition of low affinity intracellular protein–protein interactions can be addressed by this design. We have applied this strategy to develop binding partners for FBP21, a protein which is important for the splicing of pre-mRNA in the nucleus of eukaryotic cells. Firstly, by using phage display the optimized sequence WPPPPRVPR was derived which binds with K(D)s of 80 μM and 150 µM to the individual WW domains and with a K(D) of 150 μM to the tandem-WW1–WW2 construct. Secondly, this sequence was coupled to a hyperbranched polyglycerol (hPG) that allowed for the multivalent display on the surface of the dendritic polymer. This novel multifunctional hPG-peptide conjugate displayed a K(D) of 17.6 µM which demonstrates that the new carrier provides a venue for the future inhibition of proline-rich sequence recognition by FBP21 during assembly of the spliceosome.